Glycolysis and de novo fatty acid synthesis cooperatively regulate pathological vascular smooth muscle cell phenotypic switching and neointimal hyperplasia. Issue 4 (8th February 2023) - Cao, Kaixiang; Zhang, Tiejun; Li, Zou; Song, Mingchuan; Li, Anqi; Yan, Jingwei; Guo, Shuai; Wang, Litao; Huang, Shuqi; Li, Ziling; Hou, Wenzhong; Dai, Xiaoyan; et al.
Abstract: Switching of vascular smooth muscle cells (VSMCs) from a contractile phenotype to a dedifferentiated (proliferative) phenotype contributes to neointima formation, which has been demonstrated to possess a tumor‐like nature. Dysregulated glucose and lipid metabolism is recognized as a hallmark of tumors but has not thoroughly been elucidated in neointima formation. Here, we investigated the cooperative role of glycolysis and fatty acid synthesis in vascular injury‐induced VSMC dedifferentiation and neointima formation. We found that the expression of hypoxia‐inducible factor‐1α (HIF‐1α) and its target 6‐phosphofructo‐2‐kinase/fructose‐2, 6‐bisphosphatase (PFKFB3), a critical glycolytic enzyme, were induced in the neointimal VSMCs of human stenotic carotid arteries and wire‐injured mouse carotid arteries. HIF‐1α overexpression led to elevated glycolysis and resulted in a decreased contractile phenotype while promoting VSMC proliferation and activation of the mechanistic target of rapamycin complex 1 (mTORC1). Conversely, silencing Pfkfb3 had the opposite effects. Mechanistic studies demonstrated that glycolysis generates acetyl coenzyme A to fuel de novo fatty acid synthesis and mTORC1 activation. Whole‐transcriptome sequencing analysis confirmed the increased expression of PFKFB3 and fatty acid synthetase (FASN) in dedifferentiated VSMCs. More importantly, FASN upregulation was observed in neointimal VSMCs of human stenotic carotid arteries. Finally, interfering with PFKFB3 or FASN suppressed vascular injury‐induced mTORC1 activation, VSMC dedifferentiation, and neointima formation. Together, this study demonstrated that PFKFB3‐mediated glycolytic reprogramming and FASN‐mediated lipid metabolic reprogramming are distinctive features of VSMC phenotypic switching and could be potential therapeutic targets for treating vascular diseases with neointima formation. © 2023 The Pathological Society of Great Britain and Ireland.